THE INFLUENCE OF MARKETING MIX ON VEHICLE PURCHASE DECISIONS MODERATED BY GOVERNMENT POLICIES - Hendra Ditama; PM. Budi Haryono; Saparso Saparso (ID Solutions, 2022)
Marketers agree that systems can work very well when there are minimal laws governing the business. In Indonesia, the government regulates policies as rules and economic stimulus. During the COVID-19 pandemic, the Indonesian economy was in a bad state. The automotive industry experienced a drastic decline in motor vehicle sales by 95% in May 2020. PT. Maybank Indonesia Finance, which is a motor vehicle financing company, also experienced a drastic decline in sales. In the face of unfavourable economic conditions, the government issued various policies as a stimulus for economic improvement. Companies must be able to explore the role of government policies that moderate marketing strategies within the company. In this study, the marketing mix is used as an independent variable moderated by Government Policy. This quantitative research took a study at PT. Maybank Indonesia Finance, with 100 respondents who are debtors throughout Indonesia using WarpPLS data processing. The result of the research shows that Government Policy related to Price and Promotion influences the Purchase Decision.